Suplementação com óleo essencial e extrato aquoso de manjericão (Ocimum basilicum) na dieta de pacu (Piaractus mesopotamicus) - REBECA MARIA SOUSA (2024)
Aquaculture has been increasingly important to meet the growing need for fish, which has driven the intensification of farming systems. In this sense, correct feeding management is fundamental for fish, especially for Neotropical species such as pacu (Piaractus mesopotamicus) whose nutritional requirements are generally not completely established. In this context, the use of medicinal plants, such as basil (Ocimum basilicum), as food additives is attractive due to their bioactive compounds. These additives can enhance growth, reduce stress, stimulate appetite and strengthen fish immunity. The study aimed to evaluate the use of basil in two forms (essential oil and aqueous extract) as a food additive in the pacu diet, considering growth performance, muscle residue, intestinal histology and hematological parameters after simulated transport stress. Three treatments were used: (i) control diet (without incorporation of O. basilicum) (ii) 0.5% essential oil of O. basilicum incorporated into the diet; (iii) 0.5% aqueous extract of O. basilicum incorporated into the diet. Pacu juveniles (23 g ± 0.08, n=180) were distributed in the experimental units (300 L boxes) of the three treatments. Six replications (six boxes) per treatment were used. After the final biometrics at 45 days of cultivation, the fish were subjected to transport simulation for 4 hours to evaluate the effect of treatments on transport management.